2016
DOI: 10.7554/elife.15550
|View full text |Cite
|
Sign up to set email alerts
|

Small molecule proteostasis regulators that reprogram the ER to reduce extracellular protein aggregation

Abstract: Imbalances in endoplasmic reticulum (ER) proteostasis are associated with etiologically-diverse degenerative diseases linked to excessive extracellular protein misfolding and aggregation. Reprogramming of the ER proteostasis environment through genetic activation of the Unfolded Protein Response (UPR)-associated transcription factor ATF6 attenuates secretion and extracellular aggregation of amyloidogenic proteins. Here, we employed a screening approach that included complementary arm-specific UPR reporters and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

27
300
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 197 publications
(336 citation statements)
references
References 51 publications
(102 reference statements)
27
300
0
Order By: Relevance
“…Similarly, in a more recent work, it was demonstrated that ceapins, a class of pyrazole amides, blocked ATF6 signaling in response to ER stress by trapping it in the ER (126,127). On the other hand, Plate et al identified two nontoxic small molecules, compounds 147 and 263, which selectively activated the ATF6 branch of the UPR (128). They further demonstrate that those compounds reduced secretion and extracellular aggregation of destabilized amyloidogenic proteins (128).…”
Section: Er Proteostasis Control and Response To Chemotherapy And Radmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, in a more recent work, it was demonstrated that ceapins, a class of pyrazole amides, blocked ATF6 signaling in response to ER stress by trapping it in the ER (126,127). On the other hand, Plate et al identified two nontoxic small molecules, compounds 147 and 263, which selectively activated the ATF6 branch of the UPR (128). They further demonstrate that those compounds reduced secretion and extracellular aggregation of destabilized amyloidogenic proteins (128).…”
Section: Er Proteostasis Control and Response To Chemotherapy And Radmentioning
confidence: 99%
“…On the other hand, Plate et al identified two nontoxic small molecules, compounds 147 and 263, which selectively activated the ATF6 branch of the UPR (128). They further demonstrate that those compounds reduced secretion and extracellular aggregation of destabilized amyloidogenic proteins (128). Both approaches, either blocking ATF6 activation or promoting it, may therefore represent useful strategies for controlling ER proteostasis in various human diseases, including cancers.…”
Section: Er Proteostasis Control and Response To Chemotherapy And Radmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, we took advantage of the unique ability of stem cells to recapitulate many features of embryogenesis to elucidate the function of ATF6 during human stem cell differentiation. We used a newly identified small-molecule activator of ATF6 to assess how ATF6 signaling affected stem cell differentiation into early germ cell layers and functional cell types (36). Conversely, we examined how impairment of ATF6 signaling affected early human stem cell differentiation using iPSCs generated from patients that were homozygous for loss-of-function ATF6α alleles (11, 27).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, UPR has attracted the attention of many biomedical researchers, and small molecules that target UPR for therapeutic purposes have been identified or are under development (for recent reviews, see Hetz et al 40 and Maly and Papa 41 ). Recently, small molecules that target the ATF6 UPR branch with high specificity have been identified, 42,43 and the non-toxic activators of endogenous ATF6 could be of major interest in stroke (see below). In experimental brain ischemia, several strategies have been used to restore ER function impaired by ischemia.…”
mentioning
confidence: 99%